Assessment of health-related quality of life and related factors in patients with chronic liver disease - Souza, Neila Paula de [UNESP]; Villar, Livia Melo; Garbin, Artênio José Ísper [UNESP]; Rovida, Tânia Adas Saliba [UNESP]; Garbin, Cléa Adas Saliba [UNESP] (Elsevier B. V., 2015)
Assessing health-related quality of life is an important aspect of clinical practice. Thus, the present study attempts to assess the health-related quality of life of patients with chronic liver disease. A cross-sectional survey was conducted on 133 chronic liver disease patients, using three instruments: a demographic questionnaire, the Chronic Liver Disease Questionnaire, and Model for End-Stage Liver Disease index. Variables were expressed as frequencies, percentages, means, and standard deviations. The statistical analysis included Pearson's correlation, Student's t-test, and analysis of variance (p<0.05 was considered significant). The mean age of included subjects was 50.5±13.3 years. The majority were male (66.2%), Caucasian (70.7%), and had a family income of US$329-US$658.2. Over half of the patients (56.4%) were infected by hepatitis C virus and 93.2% had low Model for End-Stage Liver Disease scores. Model for End-Stage Liver Disease score was related to age (r=0.185; p=0.033). Higher mean Chronic Liver Disease Questionnaire scores were obtained for emotional function (39.70/SD±12.98) and while lower scores were obtained for abdominal symptoms (16.00/SD±6.25). Fifty-two patients (39.1%) presented overall low (<5) Chronic Liver Disease Questionnaire scores. Furthermore, Chronic Liver Disease Questionnaire score was related to family income (r=0.187, p=0.031). Most individuals presented high mean Chronic Liver Disease Questionnaire scores, indicating low health-related quality of life, especially individuals with low family income.
Keywords: Hepatitis; Liver cirrhosis; Quality of life